Prevalence of noise-induced health hazards and occupational safety practices among welders in Mysuru city: a cross-sectional study - A. J., Keerthik; Shabadi, Nayanabai; M., Mounika Sree (International Journal Of Community Medicine And Public Health, 2024)
Background: Occupational exposure to noise is a significant concern in the welding industry, posing potential health hazards to workers. This study aimed to assess the prevalence of noise-induced health hazards, knowledge regarding these hazards, and the practice of preventive measures among welders in Mysuru City. Methods: A cross-sectional study was conducted and data was collected from welders in Mysuru City, including noise exposure levels, perceived stress levels, insomnia prevalence, and demographic characteristics. The association between the number of years of noise exposure and auditory/non-auditory health effects was analysed. Participants' awareness of noise-induced health hazards and the use of protective equipment were also evaluated. Results: The study included male participants, predominantly below 30 years of age, with a majority (74.3%) belonging to the Muslim community. Decreased hearing (11.5%) and sleep disorders (3%) were reported by participants. About half (53.7%) were aware of noise-induced health hazards, with a high usage of safety glasses but limited use of earplugs. Most had exposure to noise for less than 5 years. Moderate levels of perceived stress and low prevalence of insomnia were observed. Significant associations were found between the number of years of noise exposure and both auditory/non-auditory health hazards, as well as between age category and auditory health effects. Conclusions: The study reveals the prevalence of noise-induced health hazards among welders in Mysuru City and highlights the importance of promoting occupational health and safety measures. Raising awareness and encouraging the use of protective measures are crucial to mitigate the adverse effects of noise exposure in the welding industry.